2022
DOI: 10.3389/fpubh.2021.816697
|View full text |Cite
|
Sign up to set email alerts
|

Green Growth, Green Technology, and Environmental Health: Evidence From High-GDP Countries

Abstract: Green growth is an exceptional strategy for sustainable development. It provides a pathway to combat environmental issues and the use of natural resources. This study investigates the effects of green technology and environmental factors on green growth in high-gross domestic product (GDP) countries from 2000 to 2020. In addition, it also probes the linear and nonlinear effects of GDP on green growth. To do so, we employ an advanced econometric approach, e.g., a cross-sectional autoregressive distributed lags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 79 publications
11
33
0
1
Order By: Relevance
“…Following Niu et al ( 8 ) and Hussain et al ( 21 ), this study constructed the following two models:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Niu et al ( 8 ) and Hussain et al ( 21 ), this study constructed the following two models:…”
Section: Methodsmentioning
confidence: 99%
“…For the sustainable development of a country, green growth is an exceptional strategy. In their article, Hussain et al ( 21 ) investigated the impact of green technology and the environment on the gross domestic product (GDP) of the countries from the year 2000 to 2020. Their findings suggest that green technology has a substantial effect on green growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study concluded that continues economic growth is not favorable to green growth ( 26 ). Raising how economic growth can occur in under-developed or South Asian countries of BRI can be favorable to green growth.…”
Section: The Impact Of the Chinese In-land Environmental Policiesmentioning
confidence: 99%
“…The industries installed at SEZs, automobiles, and other non-green emissions may have the same impact on green growth as those rich GDP countries ( 26 ). Then, imagine developing countries and their stagnant economies and the countries of South Asia which are already polluted countries ( 33 ).…”
Section: The Impact Of the Chinese In-land Environmental Policiesmentioning
confidence: 99%
See 1 more Smart Citation